Study on the performance of sewage sludge biochar modified by nZVI to remove Cu(II) and Cr(VI) in water. (19th September 2022) - Kang, Xudong; Xiao, Feiyu; Zhou, Sihai; Zhang, Qiuya; Qiu, Liwei; Wang, Liping
Abstract: In this study, to simultaneously dispose of sludge and wastewater containing heavy metals, sludge biochar loaded with nano zero-valent-iron (nZVI) was prepared at 700 °C (nBC700) to remove Cr(VI) and Cu(II). The results showed the removal capacity of biochar was greatly improved by loading nZVI, and the adsorption capacities of biochar for Cu(II) and Cr(VI) increased by 251.96% and 205.18%. Pseudo-second-order kinetic and Sips isotherm models were fitted to the removal processes. Intraparticle diffusion models showed the removal process was controlled by surface diffusion and intraparticle diffusion. Competitive experiments showed Cr(VI) can compete with Cu(II) for active sites, but Cr(VI) was more easily removed by nBC700 through cation bridge. The removal mechanism illustrated removing Cu(II) mainly depended on complex precipitation, followed by reduction reaction, while Cr(VI) was on the contrary. This work provided effective data for sludge disposal and heavy metal removal. HIGHLIGHTS: The sludge biochar adsorbent modified by nano zero-valent iron was prepared. Reduction and functional group complexation play a major role in the removal of Cu(II) and Cr(VI), respectively. The adsorption effect of nBC700 on Cr(VI) was better in the competitive adsorption. Cation bridge was the main reason for the better adsorption of Cr by nBC700 in the competitive adsorption. Graphical Abstract